Corporate Value, Firm Size and Firm Profitability in Listed Nigeria Consumer Goods Firms (Journal of Management and Social Sciences, 2026)
The size and value of Nigeria companies can affect how well it performs, with bigger companies often enjoying some benefits but also facing some challenges. While some experts believe that larger companies tend to be more profitable, others don’t fully agree. This study examined how a company’s size and value affect its profits, focusing on 20 consumer goods companies listed on the Nigerian Stock Exchange in 2023. The study used existing data to carry out the research. The period of study is 10 years from 2014 - 2023. The study used statistical tools of regression for analysis. The study found that there is strong positive effect of corporate value on profitability whereas firm size has no significant effect on profitability. This implies that corporate value contributes significantly to profitability of listed consumer goods firms in Nigeria in terms of return on asset. The study therefore recommended that Companies in the Nigerian consumer goods sector should focus on building and sustaining their corporate value through investor relations, transparent financial reporting, and brand strength managers should shift focus from mere expansion to operational excellence.  Keywords: Corporate value, firm size, firm profitability